BRCA Mutation Testing for First-Degree Relatives of Women With High-Grade Serous Ovarian Cancer [4OP]. (May 2018) - Kwon, Janice S.; Tinker, Anna; Hanley, Gillian; Pansegrau, Gary; Carey, Mark S.; Schrader, Kasmintan
Abstract : INTRODUCTION: Women with high-grade serous ovarian cancer (HGSC) have a 20% chance of carrying a BRCA1 or BRCA2 mutation and are eligible for BRCA testing. Many are untested, therefore their female first-degree relatives (FDR) may not qualify for testing unless they have specific ethnicity or other personal/family cancer history. We conducted a cost-effectiveness analysis to evaluate BRCA mutation testing for these FDR who are otherwise ineligible for testing. METHODS: A Markov Monte Carlo simulation model estimated the costs and benefits of 3 strategies for female FDR of HGSC patients whose BRCA status is unknown: 1) no BRCA testing; 2) universal BRCA testing, followed by risk-reducing bilateral salpingo-oophorectomy (RRBSO) for mutation carriers ("BRCA testing"); 3) universal RRBSO, without BRCA testing ("RRBSO"). Effectiveness was estimated in quality-adjusted life year (QALY) gains. Sensitivity analyses accounted for uncertainty around various parameters. The time horizon was 50 years. RESULTS: BRCA testing for female FDR of HGSC patients yielded a higher average QALY gain at acceptable cost compared to no BRCA testing, with an ICER of $7, 729 per QALY. BRCA testing was more effective and less costly than RRBSO (19.20 QALYs vs 18.48 QALYs, and $10, 108.35 vs $13, 959.20, respectively), therefore BRCA testing is the dominant strategy. Results were stable over a wide range of plausible costs and estimates. Compliance with hormone replacement therapy had to exceed 84% for RRBSO to be the preferred strategy. CONCLUSION: BRCA mutation testing should be offered to all female first-degree relatives of women with high-grade serous ovarian cancer when their BRCA mutation status is unknown.